Invariantes de germes de aplicações - Ament, Daiane Alice Henrique (Universidade Federal de São Carlos, 2017)
In this work, we show relations between invariants of map germs. First, we consider an analytic function germ f : (X, 0) —(C, 0) on an isolated determinantal singularity and we present a relation between the Euler obstruction of f and the determinantal Milnor number of f. In the particular case where (X, 0) is an isolated complete intersection singularity, we obtain a simple way to calculate the Euler obstruction of f as the difference between the dimension of two algebras. After, we work with map germs f : (X, 0) —— (C2, 0), where (X, 0) is a plane curve with isolated singularity. We introduce the image Milnor number to these map germs and we present a positive answer to the Mond’s conjecture in this context. The Mond’s conjecture proposes an inequality between two other invariants, the A^-codimension and the image Milnor number, in the case of map germs f : (Cn, 0) —(Cn+1, 0) when the dimensions (n,n + 1) is in Mather’s nice dimensions. The conjecture is true for n = 1, 2, and for the cases n > 3 is an open problem.
Keywords: Obstrução de Euler de uma função; Número de Milnor determinantal; Singularidade determinantal isolada; Número de Milnor da imagem; Curvas singulares; Euler obstruction of a function; Determinantal Milnor number; Isolated determinantal singularity; Image Milnor number; Curve singularities; CIENCIAS EXATAS E DA TERRA::MATEMATICA